The Spectrum and the Numerical Range of the Product of Finite Numbers of Automorphic Composition Operators on Hardy Space 2 - H. Abood, Eiman; N. Kadhim, Samira; M. Khalil, Sarah (Iraqi Journal of Science, 2023)
Throughout this paper we study the properties of the composition operatorCp1  op2  o…opn  induced by the composition of finite numbers of specialautomorphisms of U,pi  (z)  iip z1 p zSuch that pi  U, i  1, 2, …, n, and discuss the relation between the product offinite numbers of automorphic composition operators on Hardy space H2 and someclasses of operators.